MORBIDITY AND MORTALITY AMONG PATIENTS SUSTAINING CHEST INJURY DUE TO BLUNT FORCE - THE DIFFERENCE BETWEEN YOUNG AND ELDERLY - abid, Ambreen; Ahmad, Tanveer; Thapaliya, Pratikshya; Dawani, Surrendar; Sikander, Nazish; Mazcuri, Misauq (Journal of Ayub Medical College Abbottabad, 2020)
Background: Blunt Chest trauma (BCT) is caused by road traffic accidents (RTAs), falls, assaults, or occupational injuries. Age has been hypothesized to be a predictor of complications and adverse outcomes in the elderly. This study aimed to compare morbidity and mortality in young and elderly patients with BCT. Methods: This prospective two-arm study was conducted in Jinnah Postgraduate Medical Center, Karachi from July 1st till 31st December 2019 after approval from the Institutional review board. All hemodynamically stable patients with BCT presenting in the emergency were stratified in two groups. Group A included patients age 12-45 years; Group B were of age ‰¥65 years. Their clinical characteristics, complications, and in-hospital outcomes were compared. Data was analysed using SPSS version 16.0. Result: There were 39 (55.7%) patients in group A and 31 (44.3%) in group B. RTAs were a significant cause of BCT in Group A (p=0.01) and falls in Group B (p=0.003). Lacerations, open wound, and flail chest were significantly more common in Group A (p‰¤0.05). Complications of BCT including pneumonia and acute respiratory distress syndrome (ARDS) were significantly higher in Group B (p‰¤0.05). Group B required mechanical ventilation more often (45.2% vs. 12.8%; p=0.003). There were seven deaths in Group B (p=0.002) and none in Group A. Conclusion: Commonest cause of BCT in the elderly is falling. Similarly, the elderly are more prone to develop pneumonia, ARDS, and the need for ventilatory support. Early intervention to control pain, improve ventilation, and chest physiotherapy reduce the risk of morbidity and mortality. Keywords: Blunt trauma; Blunt chest trauma; Age difference; Young; Elderly; Outcomes